2018
DOI: 10.3389/fnins.2018.00363
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Visual Pathway and Brain Connectivity in Glaucoma: A Systematic Review

Abstract: Background: Glaucoma is a leading cause of irreversible blindness worldwide. The increasing interest in the involvement of the cortical visual pathway in glaucomatous patients is due to the implications in recent therapies, such as neuroprotection and neuroregeneration.Objective: In this review, we outline the current understanding of brain structural, functional, and metabolic changes detected with the modern techniques of neuroimaging in glaucomatous subjects.Methods: We screened MEDLINE, EMBASE, CINAHL, CEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 99 publications
(244 reference statements)
0
66
0
3
Order By: Relevance
“…The traditional view of glaucoma as pure ocular condition with damage to optic nerve head and retinal ganglion cells has been recently challenged and expanded by various advanced MRI studies, which demonstrated the presence of a diffuse neurodegeneration process across the brain, also involving nonvisual system (Nuzzi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional view of glaucoma as pure ocular condition with damage to optic nerve head and retinal ganglion cells has been recently challenged and expanded by various advanced MRI studies, which demonstrated the presence of a diffuse neurodegeneration process across the brain, also involving nonvisual system (Nuzzi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced magnetic resonance imaging (MRI) techniques represent a unique non-invasive approach to explore the pathogenic mechanisms of brain conditions. A number of recent studies on glaucoma have provided evidence of a neurodegenerative process across brain both within and beyond visual system (Nuzzi et al, 2018) and of various similarities with Alzheimer disease so that glaucoma may be no longer be considered a pure eye disease but rather a multifaceted and complex neurodegenerative condition.…”
Section: Introductionmentioning
confidence: 99%
“…The essential link that unites and connects all these identities shall be the creation of a real-time computer network. clinicobiological, especially in relation to prevention and plastic condition of peripheral and central nervous system (Nuzzi and Tridico, 2017;Nuzzi et al, 2018).…”
Section: "Hub and Spoke" Management Of Glaucomamentioning
confidence: 99%
“…Bei Störung und Zusammenbruch der Blut-Hirn-Schranke führt dies zu neuronalen Schäden, zu einer synaptischen Dysfunktion und zu einem Verlust der neuronalen Verbindungen, die zusammen in eine Neurodegeneration münden [42,43]. Diese synaptische Dysfunktion als neurodegeneratives Zeichen ist auch beim Glaukom nachgewiesen worden [9,44].…”
Section: Störung Der Blut-hirn-schranke Abnorme Flüssigkeitsströmeunclassified